The medial plantar flap: a case series - Jefferson Lessa Soares de Macedo; Simone Corrêa Rosa; Altino Vieira de Rezende Filho Neto; Adilson Alves da Silva; Alex Corcino Silva de Amorim; Izabelle Montanha Barbosa (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Reconstructive coverage of foot defects, especially those of the calcaneus region, is a unique technical challenge for the surgeon due to the high degree of specialization of the tissues involved and the relative immobility of the proximal tissues. METHODS: In the present study, we present our experience with the use of the flap based on the medial plantar artery to cover tissue defects in the foot, especially in the region of the calcaneal fat pad. Twelve medial plantar artery flaps constructed from 2001 to 2013 at the As a Norte Regional Hospital, Brasília, DF, were included. RESULTS: Of the 12 patients with the medial plantar artery flaps, 10 were men and 2 were women. The indications were traumatic tissue loss of the plantar fat pad in 10 patients and of the dorsum of the foot in two cases. All flaps were elevated as fasciocutaneous pedicle flaps based on the medial plantar artery. All the flaps healed without major complications, except one case that involved partial loss . The donor area was covered with a partial skin graft and there was one case of partial graft loss. The flap displayed a slightly lower protective sensitivity than the normal side. CONCLUSION: According to the results, the medial plantar flap is a good option for covering traumatic foot defects, especially those affecting the calcaneus. The versatility of the flap allows the coverage of defects of the calcaneus (e.g., the Achilles tendon and plantar fat pad regions), as well as those affecting the dorsum of the foot. The coverage of the plantar fat pad region with skin of similar texture and protective sensitivity confers to the medial plantar flap a large advantage over other flaps for reconstruction of this region.